Stigma among UK family carers of people living with dementia - Jem Bhatt; Katrina Scior; Charlotte R. Stoner; Esme Moniz-Cook; Georgina Charlesworth (BJPsych Open, 2022)
Background Models of caregiving seldom include the role of stigma when understanding the experiences of carers of people living with dementia.